Dissolution and solubility of the calcium-nickel carbonate solid solutions [(Ca1−xNix)CO3] at 25 °C - Chengyou Ma; Xiaoke Nong; Fan Xu; Zongqiang Zhu; Peijie Nong; Fei Luo; Shen Tang; Lihao Zhang; Zhiqiang Kang; Yinian Zhu (Geochemical Transactions)
Abstract A series of the calcium-nickel carbonate solid solutions [(Ca1−xNix)CO3] were synthesized and their dissolution in N2-degassed water (NDW) and CO2-saturated water (CSW) at 25 °C was experimentally investigated. During dissolution of the synthetic solids (Ni-bearing calcite, amorphous Ca-bearing NiCO3 and their mixtures), the Ni-calcite and the Ca-NiCO3 dissolved first followed by the formation of the Ni-bearing aragonite-structure phases. After 240–300 days of dissolution in NDW, the water solutions achieved the stable Ca and Ni concentrations of 0.592–0.665 and 0.073–0.290 mmol/L for the solids with lower Ni/(Ca + Ni) mol ratios (XNi), or 0.608–0.721 and 0.273–0.430 mmol/L for the solids with higher XNi, respectively. After 240–300 days of dissolution in CSW, the water solutions achieved the stable Ca and Ni concentrations of 1.094–3.738 and 0.831–4.300 mmol/L, respectively. For dissolution in NDW and CSW, the mean values of log IAP (Ion activity products) in the final stable state (≈ log K sp, Solubility product constants) were determined to be − 8.65 ± 0.04 and − 8.16 ± 0.11 for calcite [CaCO3], respectively; − 8.50 ± 0.02 and − 7.69 ± 0.03 for the synthetical nickel carbonates [NiCO3], respectively. In respect to the bulk composition of the (Ca1−xNix)CO3 solid solutions, the final log IAP showed the highest value when XNi = 0.10–0.30. Mostly, the mean values of log IAP increased with the increasing XNi in respect to the Ni-calcite, the Ni-aragonite and the amorphous Ca-Ni carbonate. The plotting of the experimental data on the Lippmann diagram for the (Ca1−xNix)CO3 solid solution using the predicted Guggenheim parameters of a 0 = 2.14 and a 1 = − 0.128 from a miscibility gap of XNi = 0.238 to 0.690 indicated that the solids dissolved incongruently and the final Ca and Ni concentrations in the water solutions were simultaneously limited by the minimum stoichiometric saturation curves for the Ni-calcite, Ni-aragonite and the amorphous Ca-Ni carbonate. During dissolution in NDW, the Ni2+ preferred to dissolve into the water solution and Ca2+ preferred to remain in the solid, while during dissolution in CSW for the solids with higher XNi, the Ca2+ preferred to dissolve into the water solution and Ni2+ preferred to remain in the solid. These findings provide valuable insights into understanding the mechanisms governing Ni geochemical cycle in natural environments.